Optimalisasi Kecerdasan Ganda Siswa Madrasah Aliyah (MA) di Kota Parepare - Saleh, Muhammad; Jamilah, Sitti; Said, Zainal (Al-Ulum, 2024)
This study focuses on optimizing students' potential at the State Islamic Senior High School in Parepare City. This research employs a mixed-method approach, combining quantitative and qualitative research to understand the research problem better. The research design used is the Sequential Explanatory Design. Quantitative data is analyzed using SPSS version 22 and SEMPls. The study results reveal that multiple intelligences, including verbal intelligence, mathematical intelligence, visual intelligence, kinesthetic intelligence, musical intelligence, interpersonal intelligence, intrapersonal intelligence, naturalistic intelligence, and existential intelligence, affect students' preferred subjects. This is indicated by the significance values of each variable, which are sig. < 0.05. Regarding extracurricular activities they influence verbal, logical/mathematical, kinesthetic, interpersonal, and naturalistic intelligence. However, musical and intrapersonal intelligence have no significant influence on the chosen extracurricular activities. The efforts to optimize multiple intelligences in developing students' potential begin with interviews and tests. However, the school has yet to direct students according to their specific multiple intelligences maximally.